Emergency volunteering willingness and participation: a cross-sectional survey of residents in northern China. Issue 7 (10th July 2018) - Shi, Mengli; Xu, Wei; Gao, Lijun; Kang, Zheng; Ning, Ning; Liu, Chaojie; Liang, Chao; Sun, Hong; Jiao, Mingli; Liang, Libo; Li, Ye; Cui, Yu; et al.
Abstract : Objectives: This study aimed to identify factors that influence people's willingness to volunteer and participation in emergency volunteering in northern China. Design/Setting: This study was conducted in Heilongjiang province in September and October 2014 using a mixed methods approach, which included a cross-sectional questionnaire survey on community residents and in–depth interviews with community residents and relevant organisational managers and officials in relation to emergency responses. A stratified cluster sampling strategy was employed to select questionnaire respondents. Participants: 2686 respondents completed the questionnaire survey; 19 key informants were interviewed. Primary and secondary outcome measures: Willingness to volunteer was the major concern of this study. Self-reported past experience of the participants in emergency volunteering served as a secondary outcome. Results: 65.7% of respondents were willing to volunteer in emergencies. 24.3% of respondents had participated in emergency actions. Higher levels of willingness to volunteer and participation in volunteering were found in those who resided in rural areas (OR=1.308 (1.064 to 1.608) for willingness; OR=1.518 (1.208 to 1.908) for participation), had stronger community attachment (OR=1.720 (1.429 to 2.069) for willingness; OR=1.547 (1.266 to 1.890) for participation), had higher recognition of responsibility (OR=1.981 (1.498 to 2.619) for willingness; OR=1.517 (1.177 to 1.955) for participation), demonstrated preparedness behaviour (OR=1.714 (1.424 to 2.064) for willingness; OR=1.391 (1.151 to 1.681) for participation) and were covered by injury insurance (OR=1.335 (1.102 to 1.619) for willingness; OR=1.822 (1.500 to 2.214) for participation). The in-depth interviews revealed that an inappropriate policy environment and poor volunteer organisational management were major barriers for converting willingness into actions. Conclusion: A relatively high level of willingness to volunteer in emergencies in northern China is associated with a range of individual, community and institutional factors. Efforts should be made to translate willingness into effective contributions to the emergency response system. This can be done through improving policies, regulations, coordination mechanisms and volunteer training and support.